The influence of paternal overweight on sperm chromatin integrity, fertilization rate and pregnancy outcome among males attending fertility clinic for IVF/ICSI treatment - Riffat Bibi; Sarwat Jahan; Tayyaba Afsar; Ali Almajwal; Mohammad Eid Hammadeh; Nawaf W. Alruwaili; Suhail Razak; Houda Amor (BMC, 2022)
Abstract Background Low and middle-income countries are facing a rapid increase in obesity and overweight burden, particularly in urban settings. Being overweight in men is associated with infertility and a higher risk to have a low sperm count or no sperm in their ejaculate. Despite potential limitations, this is one of few studies conducted to determine the potential risk of paternal overweight on sperm standard parameters, sperm chromatin integrity and assisted conception outcome including fertilization, embryo quality, cleavage rate, reduce blastocyst development, implantation, and cumulative live birth rate (CLBR). Methods A cross-sectional study of 750 infertile couples undergoing assisted reproduction technique at a single reproductive medicine center of Salma Kafeel Medical Centre Islamabad. Sperm from men undergoing ART were analyzed for chromatin integrity using sperm chromatin dispersion assay (SCD), Chromomycin A3 staining (CMA3), and toluidine blue (TB) staining, while other semen parameters were assessed on same day includes; standard semen parameters, reactive oxygen species (ROS), sperm deformity index (SDI), teratozoospermic index (TZI), and hypo-osmatic swelling test (HOST). Paternal body mass index (BMI) < 24.5-20 kg/m2 served as the reference group, while the male patients with BMI > 24.5-30 kg/m2 were considered to be overweight. Results In the analysis of the percentage of spermatozoa with chromatin maturity (CMA3) and chromatin integrity (TB) was reduced significantly in overweight men (p < 0.01) compared with a reference group. Increase in paternal BMI correlate with the increase in sperm chromatin damage (SCD r = 0.282, TB r = 0.144, p < 0.05), immaturity (CMA3, r = 0.79, p < 0.05) and oxidative stress (ROS) (r = 0.282, p < 0.001). Peri-fertilization effects were increased in oocytes fertilization in couples with overweight men (FR = 67%) compared with normal-weight men (FR = 74.8%), similarly, after univariant regression paternal weight remain predictor of sperm chromatin maturity, successful fertilization and CLBR. In the embryo, developmental stage number of the embryo in cleavage was higher in normal weight men, while day 3 (D3) embryos, percent good quality embryo D3, and blastocyst formation rate were compared able between the groups. The paternal overweight group had significant (p < 0.001) increased neonatal birth weight (2952.14 ± 53.64gm; within normal range) when compared with the reference group (2577.24 ± 30.94gm) following assisted reproductive technology (ART). CLBR was higher (p < 0.05) in normal weight men compared to couples with overweight male partners. CLBR per embryo transfer and per 2PN was a statistically significant (p < 0.05) difference between the two groups. An inverse association was observed in the linear regression model between paternal BMI with fertilization rate and CLBR. Conclusion The present study demonstrated the impact of paternal overweight on male reproductive health, as these patients had a higher percentage of immature sperm (CMA3) with impaired chromatin integrity (SCD, TB) in their semen and had decreased fertilization rate, CLBR following assisted reproductive treatments. The present study supports that paternal overweight should be regarded as one of the predictors for fertilization, CLBR and useful for counseling, to consider body mass index not only in women but also for men, in those couples opting for ART treatment, and warrant a poor reproductive outcome in overweight men.